ELECTRONIC VOTING PERCEPTIONS IN GHANA - IN SEARCH OF A CRITICAL MASS - Kubuga, K. K.; Laar, D. S.; Ayoung, D. A.; Asaamoning, G. (UDS International Journal of Development, 2023)
To establish Ghana’s readiness to deploy electronic voting at the national level and determine when (year) it will be socio-technically feasible to hold national elections using electronic means. The study employed the unified theory of acceptance and use of technology (UTAUT) and a self-administered questionnaire through the online survey method to collect data from 197 respondents in Ghana. The quantitative responses were coded and analysed using SPSS v25 while qualitative responses were thematically analysed. The findings indicate that Ghanaians have a strong positive perception that electronic voting system will yield more acceptable and more accurate results. They are generally sure of their personal abilities to use any future eVoting system but not sure of the abilities of other citizens. This study suggests that it would be possible to reach critical mass by the 2024 elections if stakeholders make efforts by way of education and campaigning. Partly due to COVID-19 restrictions on movement, the survey component of the research resorted to the use of electronic forms for data collection. This would invariably skew data elicitation, even though purely voluntary, towards people with good enough familiarity with digital tools. The implication of this research is the empirical evidence that the time is ripe for the implementation of electronic voting in Ghana. It paints a clearer picture of the mindset towards the acceptability of such electronic systems. Unlike previous studies where the focus is on trust (or perceptions) of the respondent on the particular electoral body (institution), this work goes further to attempt to quantity and predict the point of critical mass for acceptance of eVoting in Ghana.